Rab6A GTPase contributes to phenotypic modulation in pulmonary artery smooth muscle cells under hypoxia. Issue 5 (11th November 2018) - Wang, Fang; Xu, Xingxiang; Tang, Weian; Min, Lingfeng; Yang, Junjun
Abstract: Previous studies have demonstrated that hypoxia can induce phenotypic modulation of pulmonary smooth muscle cells; however, the mechanisms remain unclear. The present study aimed to investigate the effect of the GTPase Rab6A‐mediated phenotypic modulation and other activities of rat pulmonary artery smooth muscle cells (RPASMCs). We revealed that Rab6A was induced by hypoxia (1% O2 ) and was involved in a hypoxia‐induced phenotypic switch and endoplasmic reticulum stress (ERS) in RPASMCs. After 48 hours of hypoxia, the expression of the phenotype marker protein smooth muscle actin was downregulated and vimentin (VIM) expression was upregulated. Rab6A was upregulated after 48 hours of hypoxia, and the level of glucose‐regulated protein, 78 kDa (GRP78) after 12 hours of hypoxic stimulation was also increased. After transfection with a Rab6A short interfering RNA under hypoxic conditions, the expression levels of GRP78 and VIM in RPASMCs were downregulated. Overall, hypoxia‐induced RPASMCs to undergo ERS followed by phenotypic transformation. Rab6A is involved in this hypoxia‐induced phenotypic modulation and ERS in RPASMCs.